Evaluation du risque potentiel au niveau du bassin versant Enssa des crues d'Oued - MAKRI, FATIMA ZOHRA (University of M'sila, 2013)
The flood is rick by far the most coûrmon natural rick on the city of harrouch .For a longtime, this rick was considere{ but without any interest to the vulnerability of exposed elemeni by local authorities as dangerous. In spite of the number conducted studies on the subject and that resulteds omel ocal physical solutions,n one of theses tudiesa doptedg lobal measuresto guaranteea minimum of safety. In this memoire,w e studyt he hydraulic datah ydrological and topographicacl haracteristicso f the city of harrouch (Oued Enssa) to identifu areas at risk of flooding
Keywords: Harrouch,f lood rick, torrential rains, watershedm, aximum flow, OuedE nssa